Finds from Miletus XXXII. Clay Rings from the Sanctuary of Dionysos in Miletus - Steinmann, Lisa (Archäologischer Anzeiger, 2020)
During its excavation in the 1970s, a large number of unidentifiable objects were found in the sanctuary of Dionysos in Miletus: »Peculiar and as of now not explicable for the editor [Willi Real] are numerous fragments of flat rings […]. They are reminiscent of the rings used for modern coal stoves. […] Hitherto no interpretation has been found.« (Real 1977, 105). In the course of a re-examination of the excavation’s findings since 2017, it has been possible to find similar rings from different places in the Mediterranean. It is plausible that these until now unidentified objects are stacking rings used in potters workshops, an isolated and unique find for 5th century Miletus. In this article, the rings will be compared and classified, followed by an assessment of their functionality as well as a discussion of their context.